Pemanfaatan Internet Untuk Memvariasikan Sumber Belajar Bahasa Inggris dalam Meningkatkan Kinerja Guru - Hamidah, Fitria Nur; Yanuarmawan, Dion (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2018)
To become a qualified and professional educator, teachers at the senior high school are required to have various skills to support teaching and learning activities. The goal of this program is to provide internet mastery skills by high school teachers to facilitate the search for English learning resources and introduce and deepen the knowledge and skills of supporting websites in learning English. The Outcomes were obtained; 1.) Participants had the knowledge and skills in utilizing the Internet as a varied source of English learning. 2.) Participants were able to identify and deepen the knowledge of supporting websites in learning English. 3.) The availability of 1 handout of internet utilization training to vary the English language resources to improve teacher performance. 4.) Participants had the knowledge in utilizing the internet to vary the English learning resources as evidenced by the comparison of the final outcome of the training with the participants' initial knowledge. the average value of the theory test has increased by 80-49 = 31. While the average score of practice tests also increased by 77 - 48 = 29. It proved that the training is held successfully to improve teachers performance in using internet as a source of learning.